SOSIALISASI BAHAYA MEMBUANG SAMPAH SEMBARANGAN DAN MENENTUKAN LOKASI TPA DI DUSUN DELES DESA JAGONAYAN KECAMATAN NGABLAK - Wibisono, Arif Fajar (AJIE (Asian Journal of Innovation and Entrepreneurship), 2014)
Dusun Deles, Jogonayan village, District Ngablak, Magelang, Central Java consisting of 3 RW and 12 RT. Mostly livelihood society is a farmer. Besides his profession as a farmer, society Also worked as traders, civil servants, workers, etc. People in the Dusun Deles is people who have a high desire to advance Dusun Deles, this can be proved on the willingness of citizens to cooperate and worked -together for development in Dusun Deles. On the physical development and infrastructure which was a highlight for the citizens Deles is the concept of waste disposal sites. The concept of waste disposal sites as well as solutions to problems Deles village hygiene and raise the awareness of citizens to dispose of waste in place. The need for infrastructure in Dusun Deles is desperately needed, not just for the media spotlight that this village will progress its development but also as a useful tool to promote and support the activities of citizens.